Adaptation rearrangements of heart of young sportsmen depending on the orientation of the training activity - Ласточкін, Віктор; Ровний, Анатолій (Slobozhanskyi Herald of Science and Sport, 2016)
Viktor Lastochkin, Anatoliy Rovnyy Purpose: studying of the main parameters of morphofunctional condition of the left ventricular cavity of heart of sportsmen in the conditions of the training and competitive activity. Material & Methods: three groups of children (n=30) of 7–9, 10–12, 13–14 years old, who begin to train in sports with the manifestation of endurance and high-speed and power qualities, the qualified sportsmen at the age of 15–16 years old, who are engaged in run on 400 m with barriers, and karatekas (n=15+n=15), not engaged children of the same aged groups (n=40). The following methods of the research were applied: analysis of special literature, pedagogical supervisions, pedagogical experiment, echocardiological methods of the research. Results: the considerable connection of types of heart of young sportsmen with indicators of exercise stress of various orientations is established. Sportsmen with the optimum vegeto-rhythmic indicators have the essential advantages in adaptation morphofunctional displacements in heart and warm productivity at sportsmen with satisfactory vegetative-rhythmic indicators. Conclusions: adaptation morphofunctional displacements in activity of the cardio-respiratory system are closely connected with the prevailing orientation of the training process and can be used as the objective test of adaptation to the special loadings in sport.